Polymorphism of IGF-1/RsaI and Carcass Percentage Variation in Sumba Ongole (SO) Cattle - Agung, Paskah Partogi; Saputra, Ferdy (Universitas Halu Oleo, 2022)
Beef cattle have a different carcass percentage according to the breed. The percentage of carcass in livestock is an important indicator to determine the potential for meat obtained from cattle. IGF-1 is a gene from the growth gene family which is known to have an influence on the percentage of carcass. A total of 445 samples of Sumba Ongole cattle (156 males and 289 females) were used for genotyping using PCR-RFLP. A total of 237 carcass percentage data were obtained in this study. Data were performed using POPGENE version 1.32 and Microsoft Excel for genetic data and descriptive statistics, respectively. The intensively reared cattle have a higher carcass percentage than the cattle that were reared traditionally. The IGF-1/RsaI in the SO cattle was polymorphic with two alelles (C and T) and three genotype (CC, TT, and CT) but has low values of heterozygosity. The C allele frequency was 0.0034 and T allele frequency was 0.9966. Further studies in larger population are needed to validate the IGF1/RsaI as a candidate genetic marker in the SO cattle.